Kalman Filter Engineering Applications - Kim, Yuri V. (IntechOpen, 2023)
The purpose of this book is to present some uses of the Kalman filter (KF) in engineering activities that can produce a robust and technically acceptable result while keeping as close as possible to the optimal (most accurate) solution. KF sub-optimization is often required, due to the realities of implementation and real-life operational conditions. The book brings together the experiences of specialists from different engineering areas using the KF in their practice.